Biotransformation of 2,4-dinitrotoluene by the beneficial association of engineered Pseudomonas putida with Arabidopsis thaliana - Akkaya, Ozlem; Arslan, Ebru (Springer Heidelberg, 2019)
2,4-dinitrotoluene (2,4-DNT) is a priority environmental xenobiotic pollutant which has toxic, mutagenic, and carcinogenic properties. Thus, its biodegradation by applying recent approaches such as taking advantage of plant-bacteria interactions is crucial. In this work, the genes from Burkholderia sp. R34, necessary for 2,4-DNT degradation, were integrated into wild-type Pseudomonas putida (P. putida) KT2440 genome, and this strain, named KT.DNT, was inoculated to soil in in vitro conditions. To estimate the disappearance of 2,4-DNT in contaminated soil, samples were taken from different time intervals, extracted and analyzed using high-performance liquid chromatography (HPLC). Biotransformation of 2,4-DNT increased gradually and the degradation in soil after 14-days of treatment with the bacterium was found to be the 97.1%, indicating that the engineered strain could be a remarkable candidate for in situ bioremediation of 2,4-DNT-contaminated sites. In addition, in vitro interaction of this bacterium with a model plant, Arabidopsis thaliana (A. thaliana), enhanced lateral root and root hair formation together with dry root weight. Moreover, the initial 2,4-DNT concentration was decreased to 68% within 2 h with the plant-associated KT.DNT in liquid culture. Hence, the usage of this bacterium with plants could also be a promising application for the 2,4-DNT biotransformation.
Keywords: Pseudomonas putida; 2; 4-DNT; Degradation; Soil; Arabidopsis thaliana